KARAKTERISTIK SERTA PENGEMBANGAN PENGGUNAAN KAYU KARET DAN BAMBU UNTUK BAHAN BAKU PERUMAHAN RAKYAT DAN INDUSTRI - Arsad, Effendi (Jurnal Riset Industri Hasil Hutan, 2012)
Rubber wood and bamboo is an important natural resource to be developed as residential and industrial raw materials which are the raw material of commercial products. The presence of rubber wood and bamboo needs to be supported by the preservation and processing industry in order to be optimally utilized. Rubber wood has physical properties, mechanical and chemical equivalent of natural forest wood. properties of rubber wood used in rural as well fuel wood rafters to corral. While bamboo also has certain advantages compared to wood because it is easily preserved, processed and have a high elasticity While bamboo is used as a wall of the house after the split and created a kind of bamboo called palupuhan/gedek. Made simple, just the process of drying in the hot sun. Durability palupuhan/gedek could reach 10 years, but must be used in place are protected from rain. Without is bamboo used in as rafters to corral, ring,Â  rafter and raw material of fishery.Keywords : rubber wood, bamboo, potency, characteristic, preservative.